SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN PADA KANTOR KELURAHAN TETANDARA KECAMATAN ENDE SELATAN BERBASIS WEB - Lado, Fransiskus Ermando (STIKOM Uyelindo Kupang, 2021)
The Tetandara Village Office, South Ende District, Ende Regency, has an information system in the form of a manual and not yet automated so that it is slow in the process of adding, changing and deleting data and other resident data collections. The purpose of making the Population Administration Information System at the Tetandara Village Office is to help provide alternative solutions to problems in the Tetandara Village. The method in this research by utilizing certain techniques, namely observation, interviews and literature study. The result of this research is a set of Population Administration Information System software in Tetandara Village. The conclusion of this study is that the design of this information system provides a lot of convenience in the population administration process.